Selective Loss of Responsiveness to Exogenous but Not Endogenous Cyclic-Dinucleotides in Mice Expressing STING-R231H - Walker, Melissa M.; Kim, Soojin; Crisler, William J.; Nguyen, Kimberlie; Lenz, Laurel L.; Cambier, John C.; Getahun, Andrew (Frontiers in Immunology, 2020)
Stimulator of interferon genes (STING) plays a central role in innate immune responses to viral and intracellular bacterial infection, and cellular damage. STING is a cytosolic sensor of cyclic dinucleotides (CDNs) including those produced by pathogenic bacteria and those arising endogenously as products of the DNA sensor cGAS (e.g. 2’3’cGAMP). The two most common alternative allelic variants of STING in humans are STING-R71H-G230A-R293Q (STING-HAQ) and STING-R232H that are found in 20.4% and 13.7-17.6% of the population, respectively. To determine the biologic consequences of these genotypic variations, we generated knock-in mice containing the murine equivalents of each variant and studied their responsiveness to CDNs. Homozygous STING-HAQ (R71H-I229A-R292Q) and STING-R231H mice were found to be unresponsive all exogenous CDNs tested (ci-di-GMP, ci-di-AMP, 3’3’ cGAMP and Rp,Rp-CDA). Homozygous STING-HAQ mice also had greatly impaired responsiveness to endogenous 2’3’ cGAMP. However, homozygous STING-R231H mice are fully responsive to 2’3’cGAMP. Analysis of heterozygous mice revealed a reduced responsiveness to exogenous and endogenous CDNs in mice carrying a single copy of STING-HAQ, while STING-R231H heterozygous mice exhibit reduced responsiveness to exogenous but not endogenous CDNs. These findings confirm and extend previous reports by demonstrating differing impact of allelic variation of STING on the ability to sense and respond to exogenous and endogenous CDNs. Finally, the STING-R231H variant mouse represents a useful tool with which to examine the relative contributions of STING sensing of exogenous and endogenous CDNs in the context of bacterial infections and CDN-based cancer immunotherapeutics.